CFD simulations of Luleälven : An examination of CFD as a tool forevaluating restoration possibilities of regulated dredgedrivers - Hedberg, Mikael (Luleå tekniska universitet, Rymdteknik, 2018)
Dredged rivers remain from when lumber was floated downriver for processing and shipping purposes. This has left parts of some rivers in Sweden with shallow rocky beaches and deep central furrows. Restoration efforts of dredged unregulated rivers has shown positive results for fish populations. This report compares, by use of CFD two regulated parts of Luleälven, one dredged and one natural. The report looks at habitats where the Riverine Grayling prefers to lay its eggs and evaluates whether velocity and depth conditions could give an explanation for the lower population of the Riverine Grayling in the dredged river. For the water levels tested, usable areas exist for all cases, but the dredged river has substantially smaller areas suitable as a habitat. The river geometry seems to be the large issue for Mattisudden as its shallow wide riverbanks are not conducive to habitats for the Riverine Grayling. Surprisingly the "lower" test case for the dredged river showed a larger usable area than for the "higher" water level, for the same river and higher usable area than the natural river. For this case the water level is now so low that the shallow wide riverbanks are above the water level and only the central furrow is filled with water. This shows two avenues that can be used to improve the habitats for the Riverine Grayling, lower the water level, or raise the riverbanks.